PERBEDAAN PERUBAHAN KEKERASAN MIKRO PERMUKAAN SEMEN IONOMER KACA MODIFIKASI RESIN DAN KOMPOMER SEBAGAI BAHAN CERVICAL BARRIER PADA BLEACHING INTRAKORONAL DENGAN HIDROGEN PEROKSIDA 35% - , Irene Sulistio ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Intracoronal bleaching has undesirable effect such as external root resorption that can be prevent with cervical barrier placement. The aim of this study was to evaluate the effects of a intracoronal bleaching gel containing 35% hydrogen peroxide on surface microhardness of resin modified glass ionomer cement (RMGIC) and compomer as cervical barrier. Fourty eight cylindrical samples of RMGIC and compomer with 4 mm in thickness and 5 mm in diameter was put in a fiber glass box with cylindrical hole with 8 mm in depth and 5 mm in diameter, and divided into 6 groups each group consisted of 8 samples. Hydrogen Peroxyde 35% applied on the sample surface. Group I was RMGIC with one time application, Group II was RMGIC with three times application, Group III was compomer with one time application, Group IV was compomer with three times application, and control group of RMGIC and compomer. All of the samples were store in incubator at 37Â°C. Surface microhardness of RMGIC and compomer were tested using Vickers hardness tester (load 100 g, dwell time 15 seconds) and the results were compared using two-way analysis of variance (ANOVA). ANOVA results showed that the changes in surface microhardness caused by type of cervical barrier materials, number of bleaching application, and interaction of cervical barrier materials and bleaching application on surface microharness (p<0.05). LSD result showed there were significant differences in surface microhardness between RMGIC and compomer (p<0.05). In this study, it was concluded that RMGIC had a better surface microhardness after 35% hydrogen peroxide application.